Karakterisasi edible film pati singkong yang diinkorporasi alicin umbi lapis kucai (Allium tuberosum) pada bakso - Navi'atur Riza Al Khoirun Nisa; Edita Rizky Sahputri; Sulthona Nur Aisyah; Muslikhatul Muwakhidah; Warkoyo Warkoyo (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Meatballs are processed meat products with a short shelf life because they are easily damaged, which is less than 8 hours at room temperature. To overcome this problem, meatball producers often take an alternative by adding harmful preservatives such as borax and formalin. Technological advances can provide solutions, namely packaging that can be eaten and made from processed products from substitute packaging that is difficult to increase or harm the body, namely edible film. The use of starch-based packaging with the addition of antimicrobial compounds, namely Allicin from chives extract is a good alternative to increase the durability and quality of meatballs during storage.This study aims to reduce the use of plastic packaging and extend the life of meatballs by using edible film packaging. This study used a RAKwhich was composed of 2 factors and each consisted of 3 levels. The first factor was the concentration of cassava starch (1 %, 2 %, and 3 % w/v) while the second factor was the concentration of chives extract (3 %, 5 %, and 7 % v/v) into the edible coating as an antimicrobial packaging for meatballs. The results showed that the characteristics of theedible film were influenced by the concentration of starch and chives extract. The best meatballs, namely 3 % starch coated meatballs and 7 % chives extract, obtained quality active edible films and increased the shelf life of meatballs at room temperature for 48 hours (6x longer than meatballs without coating ) which are safe for consumers. These results indicate that the application of alicin from chives extract as an edible coating has a tensile strength value (0.71 MPa), elongation (41.50 %), WVTR (3.65 g/m2/24hours), thickness (0.24 mm), zone of inhibition (3.29 mm), and was effective in controlling the microbiological growth of meatballs.